2005
DOI: 10.1081/imm-200055820
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Serum Measurement of IgG, IgA, IgM, and IgE Antibody Responses to Therapeutic Biologicals

Abstract: Analytical methods characterizing the immunogenicity of therapeutic proteins are useful for monitoring, characterizing and predicting reactions to biopharmaceuticals. A multiplexed assay capable of isotyping the specific IgG, IgA, IgM and IgE (IgGAME) antibody responses against a biotherapeutic was demonstrated in a hyper-immunized cynomolgus monkey, over a 15-month period. The quantitative range of the antibody measurements was determined to be 15 ng/ml to 50 ng/ml in 10% serum. By the use of any biotinylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Serum IgG, IgA and IgM are the molecular basis of humoral immune responsesplaying a role in specific immunity responses. In addition, IgG and IgM can activate the classical pathway of complement to take part in non-specific immunity responses 25 .…”
Section: Mass Spectrometry (Esi-ms)mentioning
confidence: 99%
“…Serum IgG, IgA and IgM are the molecular basis of humoral immune responsesplaying a role in specific immunity responses. In addition, IgG and IgM can activate the classical pathway of complement to take part in non-specific immunity responses 25 .…”
Section: Mass Spectrometry (Esi-ms)mentioning
confidence: 99%
“…McCutcheon et al . developed a multiplexed ADA isotyping assay in cynomolgus monkeys treated with Raptiva (humanized monoclonal antibody to CD11a) ( 15 ). The study showed the ability to measure IgG, IgM, IgA, and IgE ADA antibodies in a single assay format.…”
Section: Introductionmentioning
confidence: 99%